IDEOLLOGI TOKOH UTAMA DALAM NOVEL RIHLAH ILA ALLAH KARYA NAJIB AL-KAILANY: ANALISIS HEGEMONI GRAMSCI - , Farida Rahmawati; , Prof. Dr. Faruk, S.U., ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research is entitled The Ideology of the Main Character in the Novel Rihlah Ila Allah by Naji<b Al-Kaila<niy: A Gramsci's Hegemonial Analysis. The background of this research is the controversy between Islam and secularism happened in Egypt, which was represented by IM and the revolutionary government of Jamal 'Abdul Nashir. Rihlah Ila Allah depicts the ideas as well as the fought of ideology involved there. This research aims at investigating the involvement of the novel Rihlah Ila Allah during the fought and negotiation between Islam and secularism. To analyse that, theory of hegemony stated by Gramsci is used here. From this research, it is revealed that Rihlah Ila Allah wins secularism. This is shown from the number of episodes presented in this novel, where the episodes containing the idea about secularism are more than the episodes containing the idea about Islam. The same is so in the plot development, where the idea about secularism is predominantly presented. However, Rihlah Ila Allah still admits the truth of Islam so that it provides possibility of acceptance by IM and its supporters. Still, such truth is bordered only as a motivation to operate the social, economic, and political life.